Self-supporting alloy negative electrode and preparation method thereof

By adopting a three-layer structure self-supporting alloy negative electrode, the problems of slow kinetics of magnesium-embedded lithium and volume expansion during circulation are solved, and a lithium-ion battery negative electrode material with high energy density, excellent magnification and safety performance are achieved.

CN119480908APending Publication Date: 2025-02-18AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411518469.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The theoretical specific capacity of graphite anode materials of existing lithium-ion batteries is limited. As a negative electrode material with high specific capacity, magnesium has slow lithium embeddedness kinetics, and the volume expansion and lithium-ion evolution phenomenon during the cycle process is severe, which limits its use in high-energy-density batteries. Application in.

Method used

The self-supporting alloy negative electrode with a three-layer structure includes an insulating layer, copper foil and active material layer. The active material layer is a porous structure, including a biphasic alloy material and a colloidal electrolyte, and is prepared by direct current electrodeposition, scraping and co-deposition. , eliminating traditional complex process steps.

Benefits of technology

The high volume/mass ratio energy, excellent rate performance, cycle performance and safety performance of the magnesium negative electrode are achieved, which significantly improves the reaction kinetics of magnesium and reduces the safety risks of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a self-supporting alloy negative electrode and a preparation method thereof. The negative electrode is a composite material containing metal, an intermetallic compound and a high polymer material. The preparation method comprises the following steps: firstly, preparing a copper foil with a circular through hole structure through a direct current electrodeposition method, then coating a layer of polymer insulating film on one surface of the copper foil, and then depositing a layer of dual-phase alloy negative electrode active material on the other surface of the copper foil through a double-target co-sputtering method. And dropwise adding a colloidal electrolyte on the surface of the active material, curing at a certain temperature, and finally pre-embedding lithium to obtain the final alloy negative electrode. The prepared alloy negative electrode has outstanding electrochemical performance: the gram volume is higher than 1000mAh / g, the lithium intercalation and deintercalation potential is lower than 0.5 V (Vs Li / Li < + >), and the alloy negative electrode has high volume and mass energy density; the cycle life is long, and the material can stably circulate for more than 100 cycles; the growth of lithium dendrites can be inhibited, the risk of short circuit is avoided, and the safety is high. The preparation method of the electrode material is simple, and industrial large-scale production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a self-supporting alloy negative electrode and a preparation method thereof, belonging to the technical field of new energy materials. Background Art

[0002] Currently, commercial lithium-ion batteries still use graphite negative electrode materials. Limited by its theoretical specific capacity of 372mAh / g, traditional lithium-ion batteries are approaching a bottleneck in improving energy density. To address this problem, scholars have studied various alloy electrode materials, including Si-based materials, transition metal oxides, metal alloys, and layered metal sulfides, in order to replace graphite negative electrode materials and meet the needs of the next generation of high energy density batteries. Among these candidate materials, magnesium has a high specific capacity (3,350mAh / g, 3,832mAh / cm 3 ), low reaction voltage (lithiation voltage is about 18mV, delithiation voltage is about 50mV), and small structural change when reacting with lithium (alleviating the charge and discharge voltage hysteresis phenomenon) have attracted much attention. In addition, magnesium metal is also an environmentally friendly and resource-rich material. Although magnesium is attractive enough as a negative electrode material, the slow lithium insertion kinetics seriously hinders the electrochemical reaction of magnesium. Coupled with the lower lithium insertion platform, the lithium insertion process is more difficult and even more prone to lithium precipitation. Studies have shown that at current densities above 10mA / g, magnesium and lithium cannot undergo alloying reactions. Nanostructure design is considered to be an effective strategy to solve the above problems. However, in order to ensure the integrity and electronic conductivity of nanoporous electrodes, a large amount of binders and conductive additives are often required. These inactive components will significantly reduce the energy density of the electrode. In addition, the volume expansion problem during the cycle of alloy negative electrodes also limits its development. Therefore, the development of high-capacity, high-rate, long-cycle, and high-safety magnesium negative electrodes still faces severe challenges. Summary of the invention

[0003] The present invention is designed to solve the above technical problems and provides a self-supporting alloy negative electrode and preparation method. The purpose is to use simple technical means to eliminate the complicated process steps such as slurry preparation and coating in the traditional electrode preparation method, and to prepare a flexible electrode without any auxiliary components (binders and conductive agents, etc.), thereby improving the reaction kinetics of magnesium. The electrode prepared by this technical solution has high volume / mass specific energy and excellent rate performance, cycle performance, and safety performance. The electrode has great engineering application prospects.

[0004] The objective of the present invention is achieved through the following technical solutions:

[0005] The technical solution of the present invention provides a self-supporting alloy negative electrode, characterized in that: the alloy negative electrode is a three-layer structure, which is an insulating layer, a copper foil, and an active material layer in sequence, wherein the active material layer is a porous structure with a thickness of 2 to 5 um, and includes a dual-phase alloy material and a colloidal electrolyte.

[0006] In addition, the material of the insulating layer includes a film-forming agent and a curing cross-linking agent, wherein the film-forming agent is one or a mixture of polyurethane, epoxy resin, acrylic acid, and LA133; the curing cross-linking agent is one or a mixture of polyisocyanate, aziridine type and epoxy type curing cross-linking agents; the proportion of the film-forming agent in the glue of the insulating layer material is 0.1wt% to 1wt%, the proportion of the curing cross-linking agent in the glue of the insulating layer material is 0.1wt% to 1wt%, and the thickness is 10 to 200nm.

[0007] In addition, the copper foil has a thickness of 3 to 10 um, and circular holes are distributed on its surface, with a hole diameter of 5 to 50 um.

[0008] In addition, the dual-phase alloy material contains Mg and Mg 2 Sn two phases, in which the molar number of Mg is higher than twice the molar number of Sn.

[0009] In addition, the colloidal electrolyte components are PVDF-HFP and LiTFSI.

[0010] The technical solution of the present invention provides a method for preparing the above-mentioned self-supporting alloy negative electrode, characterized in that the steps of the preparation method are as follows:

[0011] Step 1: preparing a copper foil with circular holes by direct current electrodeposition;

[0012] Step 2: Apply a layer of insulating glue on one side of the copper foil by a scraping method, wherein the glue solvent is deionized water, and dry the copper foil after coating at a temperature of 100 to 150°C;

[0013] Step 3: Place the other side of the copper foil upward on the sample stage of a high vacuum magnetron sputtering instrument, evacuate the sample, and then fill it with argon gas. Use Mg and Sn as target materials to co-deposit an active material layer.

[0014] Step 4: dripping colloidal electrolyte onto the surface of the active material layer to allow the electrolyte to penetrate into the pores of the active material layer, and heat treating in a vacuum oven;

[0015] Step 5: Precharge the active material layer through direct current lithium insertion to obtain the final self-supporting alloy negative electrode.

[0016] In the implementation, the anode in step 1 is a titanium plate with round holes on the surface, and the round holes are filled with polytetrafluoroethylene. The working current density during electrodeposition is 20 to 60A / dm2 .

[0017] During implementation, the vacuum degree of the vacuum pumping in step 3 is 10 -4 ~10 -3 Pa, pressure after filling with argon gas 10 -1 ~1Pa, the working power is a radio frequency power supply; the working power of the Mg target is 100~150W, the working power of the Sn target is 10~50W, and the co-deposition time is 1~5h.

[0018] During implementation, the composition and mass ratio of the colloidal electrolyte in step 4 are: PVDF-HFP:LiTFSI=1-1.5, and the solvent is THF solution.

[0019] During implementation, the lithium insertion current in step 5 is 0.1-0.5 mA / cm 2 , the lithium insertion capacity is 100~300mAh / g.

[0020] In the above preparation method, a copper foil with a certain thickness and circular through holes on the surface is obtained by a controllable electrodeposition method in step 1. The copper foil is a flexible mechanical component that carries two functional layers and also plays a role in transmitting current.

[0021] The anode in step 1 is a titanium plate with circular micropores on the surface, and the circular micropores are filled with polytetrafluoroethylene. The working current density during electrodeposition is 20 to 60A / dm 2 . Through the design improvement of the anode plate, the pore size and pore distribution are controllable. The circular hole reduces the stress around the hole and ensures the tensile strength of the copper foil. The optimized design of parameters such as working current density balances the contradiction between copper foil density, crystal defects and preparation efficiency.

[0022] In step 2, a certain thickness of insulating layer is applied on one side of the copper foil to suppress the Li + Direct deposition of the interfacial layer induces Li + The interface film has high flexibility and is resistant to acid and alkali corrosion, and can exist stably in the electrolyte.

[0023] The insulating glue in step 2 contains a film-forming agent and a curing cross-linking agent. The film-forming agent is one or a mixture of polyurethane, epoxy resin, acrylic acid, and LA133; the curing cross-linking agent is one or a mixture of polyisocyanate, aziridine type and epoxy type curing cross-linking agents. The proportion of the film-forming agent in the glue is 0.1wt% to 1wt%, and the proportion of the curing cross-linking agent in the glue is 0.1wt% to 1wt%. The glue solvent is deionized water. The drying temperature after coating is 100 to 150°C. Through the optimization design of material selection and parameters, the uniform casting and rapid chemical film formation of the mixed glue on the surface of the copper foil are guaranteed. The uniform insulating adhesive film formed has strong adhesion to copper and is stably present in the electrolyte.

[0024] A certain amount of active alloy material is deposited on the other side of the copper foil through step 3. By co-deposition of Mg and Sn, an in-situ preparation containing Mg and Mg 2 Sn dual-phase alloy material. Both phase materials have high specific capacity. By introducing sufficient phase boundaries, the reaction kinetics of the two phases are improved, stress is relieved, and the cycle stability of the active material is improved.

[0025] Step 3: The vacuum degree of the sample after being placed in the working chamber is 10 -4 ~10 -3 Pa, pressure after filling with argon gas 10 -1 ~1Pa, the working power is RF power. The working power of Mg target is 100~150W, the working power of Sn target is 10~50W, and the co-deposition time is 1~5h. Through RF sputtering, Mg and Sn are embedded and deposited, which improves the bonding force between the deposited elements and the copper matrix and itself. The optimized design of process parameters ensures Ar + The bombardment efficiency is improved, which improves the deposition efficiency and quality.

[0026] In step 4, electrolyte is dripped on the surface of the active material layer to fully penetrate into the pores, and heat treated at a certain temperature to solidify it, which inhibits the cracking and pulverization of the alloy material during the cycle and improves the cycle stability of the electrode. + conductivity, driving the Li + Insertion / extraction reaction.

[0027] The electrolyte in step 4 contains substances and contents of PVDF-HFP:LiTFSI=1-1.5, and the solvent is THF solution. The optimized design of the parameters ensures the flexibility and high lithium ion conductivity of the electrolyte.

[0028] Through the pre-lithiation of step 5, lithium is dissolved in the two-phase material to form a gradient material. The lithium concentration of the active material particles decreases from the surface to the inside, thus providing sufficient driving force and improving the lithium insertion kinetics.

[0029] The lithium insertion current in step 5 is 0.1-0.5 mA / cm 2 , the lithium insertion capacity is 100~300mAh / g. The optimized design of this parameter ensures that Li + The stable, uniform and sufficient pre-embedded alloy material in the bulk phase ensures the formation of a continuous gradient and drives the Li + Embedding.

[0030] The technical solution of the present invention can produce a self-supporting alloy negative electrode by a simple method. Compared with the prior art, the characteristics and beneficial effects of the technical solution of the present invention are as follows:

[0031] (1) The preparation method is simple, eliminating the complex process steps of slurry preparation and coating in the traditional porous electrode technology solution, and is suitable for large-scale production. It has the characteristics of self-support, flexibility, and high capacity, and is suitable for a variety of lithium battery systems such as traditional liquid batteries, solid-state batteries, and flexible batteries.

[0032] (2) The insulating layer (facing the separator) avoids Li + Lithium dendrites are deposited and grown on this side, inducing Li + The lithium ions are transferred to the active layer to undergo alloying reaction. Therefore, even if lithium dendrites grow, they are on the side away from the diaphragm, which greatly avoids the risk of battery short circuit and significantly improves the safety of the battery.

[0033] (3) The uniform circular through-hole structure of the copper foil ensures the uniform flow of lithium ions, facilitates the uniform reaction of the alloy layer, and inhibits the uneven deposition of lithium. In addition, the circular holes offset the defect stress, ensure the tensile properties of the material, and reduce the surface density of the current collector.

[0034] (4) During the co-deposition process, Mg and Sn form Mg and Mg in situ 2 Sn two-phase alloy material, with nano-scale active particles and porous interface layer, has high reactivity. Both phase materials have high capacity and stable electrochemical reaction structure (suppressing voltage hysteresis). The introduction of phase boundary can greatly improve the kinetic reaction of both. At the same time, as a stress buffer area, it relieves the internal stress caused by volume expansion, suppresses the rupture and even crushing of active particles, and improves the cycle life of the electrode.

[0035] (5) The colloidal electrolyte acts as a flexible phase, which inhibits the volume change of the alloy material during the lithium insertion and extraction process, prevents the active layer from being crushed and peeled off, and ensures the electronic conduction of the active layer. + conductivity, providing sufficient Li + Diffusion channels drive the alloy reaction.

[0036] (6) Pre-lithiation process, Mg and Mg2 Sn and Li undergo solid solution reaction to form a gradient material. The lithium content decreases continuously from the surface to the inside. The concentration difference provides sufficient driving force to improve the Li + The kinetics of lithium insertion and deintercalation. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0038] Example 1

[0039] The steps of preparing the alloy negative electrode material by the method of the present invention are as follows:

[0040] Step 1: Prepare a microporous copper foil with a thickness of 9 μm by direct current electrodeposition. The pore size is 15 μm. The working current density during electrodeposition is 30 A / dm 2 .

[0041] Step 2: Apply a layer of insulating glue on one side of the copper foil by scraping and drying at a certain temperature. The film former is polyurethane, and the curing cross-linking agent is polyisocyanate. The proportion of the film former in the glue is 0.5wt%, the proportion of the curing cross-linking agent in the glue is 0.5wt%, and the glue solvent is deionized water. The drying temperature after coating is 120℃.

[0042] Step 3: Place the foil with the other side facing up on the sample stage of the high vacuum magnetron sputtering instrument and evacuate it, then fill it with a certain amount of high-purity argon gas. Using Mg and Sn as target materials, co-deposit at a certain power for a certain time to obtain an active material layer. The vacuum degree after the sample is placed is 10 -4 Pa, pressure after filling with argon gas 10 -1 Pa, the working power is RF power. The working power of Mg target is 150W, the working power of Sn target is 30W, and the co-deposition time is 2h.

[0043] Step 4: Add colloidal electrolyte to the surface of the alloy layer, allow the electrolyte to penetrate into the pores of the active layer, and dry in a vacuum oven for a certain period of time. The electrolyte contains substances and contents of PVDF-HFP:LiTFSI=1.2, and the solvent is THF solution.

[0044] Step 5: Precharge the active material to a certain capacity by direct current lithium insertion to obtain the final alloy negative electrode material. The lithium insertion current is 0.1 mA / cm 2 , the lithium insertion capacity is 100mAh / g.

[0045] Example 2

[0046] The steps of preparing the alloy negative electrode material by the method of the present invention are as follows:

[0047] Step 1: Prepare a microporous copper foil with a thickness of 9 μm by direct current electrodeposition. The pore size is 10 μm. The working current density during electrodeposition is 20 A / dm 2 .

[0048] Step 2: Apply a layer of insulating glue on one side of the copper foil by scraping and drying at a certain temperature. The film former is polyurethane, and the curing cross-linking agent is polyisocyanate. The proportion of the film former in the glue is 0.6wt%, the proportion of the curing cross-linking agent in the glue is 0.4wt%, and the glue solvent is deionized water. The drying temperature after coating is 130℃.

[0049] Step 3: Place the foil with the other side facing up on the sample stage of the high vacuum magnetron sputtering instrument and evacuate it, then fill it with a certain amount of high-purity argon gas. Using Mg and Sn as target materials, co-deposit at a certain power for a certain time to obtain an active material layer. The vacuum degree after the sample is placed is 10 -4 Pa, pressure after filling with argon gas 10 -1 Pa, the working power is RF power. The working power of Mg target is 130W, the working power of Sn target is 35W, and the co-deposition time is 2.5h.

[0050] Step 4: Add colloidal electrolyte to the surface of the alloy layer, allow the electrolyte to penetrate into the pores of the active layer, and dry in a vacuum oven for a certain period of time. The electrolyte contains substances and contents of PVDF-HFP:LiTFSI=1.1, and the solvent is THF solution.

[0051] Step 5: Precharge the active material to a certain capacity by direct current lithium insertion to obtain the final alloy negative electrode material. The lithium insertion current is 0.1 mA / cm 2 , the lithium insertion capacity is 200mAh / g.

[0052] Example 3

[0053] The steps of preparing the alloy negative electrode material by the method of the present invention are as follows:

[0054] Step 1: Prepare a microporous copper foil with a thickness of 9 μm by direct current electrodeposition. The pore size is 10 μm. The working current density during electrodeposition is 40 A / dm 2 .

[0055] Step 2: Apply a layer of insulating glue on one side of the copper foil by scraping and drying at a certain temperature. The film former is polyurethane, and the curing cross-linking agent is polyisocyanate. The proportion of the film former in the glue is 0.4wt%, the proportion of the curing cross-linking agent in the glue is 0.6wt%, and the glue solvent is deionized water. The drying temperature after coating is 100℃.

[0056] Step 3: Place the foil with the other side facing up on the sample stage of the high vacuum magnetron sputtering instrument and evacuate it, then fill it with a certain amount of high-purity argon gas. Using Mg and Sn as target materials, co-deposit at a certain power for a certain time to obtain an active material layer. The vacuum degree after the sample is placed is 10 -4 Pa, pressure after filling with argon gas 10 -1 Pa, the working power is RF power. The working power of Mg target is 120W, the working power of Sn target is 30W, and the co-deposition time is 2h.

[0057] Step 4: Add colloidal electrolyte to the surface of the alloy layer, allow the electrolyte to penetrate into the pores of the active layer, and dry in a vacuum oven for a certain period of time. The electrolyte contains substances and contents of PVDF-HFP:LiTFSI=1.1, and the solvent is THF solution.

[0058] Step 5: Precharge the active material to a certain capacity by direct current lithium insertion to obtain the final alloy negative electrode material. The lithium insertion current is 0.1 mA / cm 2 , the lithium insertion capacity is 150mAh / g.

Claims

1. A self-supporting alloy negative electrode, characterized in that: The alloy negative electrode has a three-layer structure, which is an insulating layer, a copper foil, and an active material layer in sequence. The active material layer has a porous structure with a thickness of 2 to 5 μm and includes a dual-phase alloy material and a colloidal electrolyte.

2. The self-supporting alloy negative electrode according to claim 1, characterized in that: The material of the insulating layer includes a film-forming agent and a curing cross-linking agent, wherein the film-forming agent is one or a mixture of polyurethane, epoxy resin, acrylic acid, and LA133; the curing cross-linking agent is one or a mixture of polyisocyanate, aziridine type and epoxy type curing cross-linking agents; the proportion of the film-forming agent in the glue liquid of the insulating layer material is 0.1wt% to 1wt%, the proportion of the curing cross-linking agent in the glue liquid of the insulating layer material is 0.1wt% to 1wt%, and the thickness is 10 to 200nm.

3. The self-supporting alloy negative electrode according to claim 1, characterized in that: The copper foil has a thickness of 3 to 10 um, and circular holes are distributed on its surface, with a hole diameter of 5 to 50 um.

4. The self-supporting alloy negative electrode according to claim 1, characterized in that: The dual-phase alloy material comprises two phases of Mg and Mg2Sn, wherein the molar number of Mg is higher than twice the molar number of Sn.

5. The self-supporting alloy negative electrode according to claim 1, characterized in that: The colloidal electrolyte components are PVDF-HFP and LiTFSI.

6. A method for preparing the self-supporting alloy negative electrode according to claim 1, characterized in that: The steps of the preparation method are as follows: Step 1: preparing a copper foil with circular holes by direct current electrodeposition; Step 2: Apply a layer of insulating glue on one side of the copper foil by a scraping method, wherein the glue solvent is deionized water, and dry the copper foil after coating at a temperature of 100 to 150°C; Step 3: Place the other side of the copper foil upward on the sample stage of a high vacuum magnetron sputtering instrument, evacuate the sample, and then fill it with argon gas. Use Mg and Sn as target materials to co-deposit an active material layer. Step 4: dripping colloidal electrolyte onto the surface of the active material layer to allow the electrolyte to penetrate into the pores of the active material layer, and heat treating in a vacuum oven; Step 5: Precharge the active material layer through direct current lithium insertion to obtain the final self-supporting alloy negative electrode.

7. The method for preparing a self-supporting alloy negative electrode according to claim 6, characterized in that: The anode in step 1 is a titanium plate with round holes on the surface, and the round holes are filled with polytetrafluoroethylene. The working current density during electrodeposition is 20-60A / dm 2 .

8. The method for preparing a self-supporting alloy negative electrode according to claim 6, characterized in that: The vacuum degree of the vacuum pumping in step 3 is 10 -4 ~10 -3 Pa, pressure after filling with argon gas 10 -1 ~1Pa, the working power is a radio frequency power supply; the working power of the Mg target is 100~150W, the working power of the Sn target is 10~50W, and the co-deposition time is 1~5h.

9. The method for preparing a self-supporting alloy negative electrode according to claim 6, characterized in that: The composition and mass ratio of the colloidal electrolyte in step 4 are: PVDF-HFP:LiTFSI=1-1.5, and the solvent is THF solution.

10. The method for preparing a self-supporting alloy negative electrode according to claim 6, characterized in that: The lithium insertion current in step 5 is 0.1-0.5 mA / cm 2 , the lithium insertion capacity is 100~300mAh / g.

Citation Information

Cited By

  • Preparation method of flexible alloy negative electrode with embedded structure

    CN120637404A